Structure‐Tuned Lead Halide Perovskite Nanocrystals. Issue 3 (24th November 2015) - Hassan, Yasser; Song, Yin; Pensack, Ryan D.; Abdelrahman, Ahmed I.; Kobayashi, Yoichi; Winnik, Mitchell A.; Scholes, Gregory D.
Abstract : Colloidally stable suspensions of lead halide perovskite nanocrystals are prepared from high‐quality lead halide nanocrystal seeds. Perovskite nanocrystals with different layered crystal structures are reported. These systems are well suited for investigations of the intrinsic photophysics and spectroscopy of organic–inorganic metal halide perovskites.